Matching with transfers: The economics of loves and marriage - Chiappori, Pierre-Andre (New Jersey Princeton University Press, 2017)
Over the past few decades, matching models, which use mathematical frameworks to analyze allocation mechanisms for heterogeneous products and individuals, have attracted renewed attention in both theoretical and applied economics. These models have been used in many contexts, from labor markets to organ donations, but recent work has tended to focus on (3z(Bnontransferable(3y (Bcases rather than matching models with transfers.s